Association between ESRα and ESRβ polymorphisms and prostate cancer risk: meta-analysis - Bai, Xiaohui; Gao, Li; Zhao, Jiawei; Liao, Wentao; Chen, Yujing; Guo, Xiaotong; Jin, Jiamin; Ge, Bo (Frontiers in Oncology, 2025)
BackgroundGene polymorphisms of ESRα Pvull(rs2234693), Xbal(rs9340799), and ESRβ Alul(rs4986938) and RsaI (rs1256049), have been investigated for their associations with prostate cancer risk. However, the nature of these relationships remains ambiguous. Therefore, the present study aimed to further clarify the association between ESR gene polymorphisms and prostate cancer.ObjectiveTo investigate the association between ESRα Pvull(rs2234693), Xbal(rs9340799), and ESRβ Alul(rs4986938), Rsal(rs1256049) polymorphisms and prostate cancer risk.Materials and methodsPubMed, Medline, and CNKI were searched. Associations were assessed using odds ratios (ORs) with 95% confidence intervals (CIs). The false-positive report probability (FPRP), Bayesian false discovery probability (BFDP), and Venetian criteria were used to evaluate the credibility of statistically significant findings.ResultsWe found for the first time that, overall, the ESRα PvuII polymorphism was significantly associated with a reduced risk of prostate cancer (pp vs. Pp + PP: OR = 0.83, 95% CI = 0.71–0.97; pp vs. PP: OR = 0.75, 95% CI = 0.57–0.99; p vs. P: OR = 0.88, 95% CI = 0.78–0.99). A similarly reduced risk was observed in Caucasians (pp + Pp vs. PP: OR = 0.01, 95% CI = 0.01–0.04). By contrast, the ESRαPvuII polymorphism increased prostate cancer risk among Africans (pp + Pp vs. PP: OR = 2.38, 95% CI = 1.61–3.51). For ESRβ RsaI, we observed a reduced risk of prostate cancer in Asians (r vs. R: OR = 0.87, 95% CI = 0.77–0.98). However, no significant associations were identified for ESRα XbaI or ESRβ AluI. When evaluating credibility using the FPRP, BFDP, and Venetian criteria, no statistically robust associations were confirmed.ConclusionsOverall, the results suggest a potential association between the ESRα PvuII and ESRβ RsaI polymorphisms and prostate cancer risk, although the credibility assessments did not support statistically robust relationships.